ANALISA OPTIMASI JARINGAN JALAN BERDASAR KEPADATAN LALU LINTAS JALAN RAYA - Gaguk Suliswanto; Zulkifli Lubis (Litbang Pemas - Universitas Islam Lamongan, 2017)
Increasing the population, the number of vehicles, and activities in Gresik Town causing social and economic problems that are highly dependent on road transport. These problems arise because of the imbalance problems such as the high volume of traffic and the increasing number of people living along the Gubernur Suryo Road. The method used in this research is descriptive study. This method used to look for the amount of capacity and degree of saturation that affect the activities on this road. Data collection techniques using observation and geometric data. While the flow of vehicles using MKJI 1997 method. From the effectiveness side, the road capacity is smaller than planned capacity due to the side barriers and the growth rate of the vehicle in line with the population increase. From the identification of problems, volumes of traffic is high, amounted 2969 smp/hour. Performance of road being dropped LOS = 1.91 (F), due to the high volume of traffic that passing through this road is not comparable with the capacity (1548.36 smp/hour) and Degree of Saturation (DS) greatly affects the traffic flow on Gubernur Suryo Road of = 1.91 smp/hour. The high delay and side barrier amounted 317 smp/hour. Side barrier can be resulted from the calculation of total amount divided by the capacity, the result is 0,20 smp/hour. It affects the smoothness of traffic flow because the density of traffic and intersection of roads are not well planned, where the distance of each t-junction is quite far one another. Traffic engineering is used to solve the traffic jam problems on the Gubernur Suryo Road and along the market road. It is expected that the government can curb the tricycles parking and vehicles along the road so that traffic jam can be resolved soon.